Acute venous thromboembolic events in patients with monoclonal gammopathy of undetermined significance: An analysis of the National Inpatient Sample. Issue 225 (May 2023) - Abdelhay, Ali; Mahmoud, Amir A.; Mostafa, Mariam; Al Ali, Omar; Gill, Simrat; Jamshed, Saad
Abstract: Background: Monoclonal Gammopathy of Undetermined Significance (MGUS) is a premalignant plasma cell disorder which despite being clinically silent carries an increased risk of venous thromboembolism (VTE). We conducted a population-based study to investigate the risk of VTE in these patients. Methods: We utilized the National Inpatient Sample (NIS) for the year 2016 to compare the incidence of acute VTE between patients who carry the diagnosis of MGUS and those who don't. We excluded hospitalizations with age < 18 years and those that had a diagnosed lymphoma, leukemia, solid malignancy, or other plasma cell dyscrasia. We utilized the ICD-10-CM coding system to search the database for codes of VTE, MGUS, and other comorbid conditions. Multivariate logistic regression models were used for comparative analysis adjusting for demographic characteristics and comorbidities. Baseline comorbidities were described as frequencies and proportions for categorical variables and as medians with interquartile ranges for continuous variables. Results: A total of 33, 115 weighted hospitalizations were included in the MGUS group. These were compared to 27, 418, 403 weighted hospitalizations without the diagnosis of MGUS. The MGUS group had higher odds of composite venous thromboembolism (adjusted OR 1.33, 95 % CI 1.22–1.44), deep vein thrombosis (adjusted OR 1.46, 95 % CI 1.29–1.65), and pulmonary embolism (adjusted OR 1.22, 95 % CI 1.09–1.37). Conclusion: Patients with MGUS had increased odds of developing acute venous thromboembolism compared to patients with no history of MGUS. Highlights: MGUS may be linked to venous thromboembolism including DVT and pulmonary embolism. The overall risk of venous thromboembolism in MGUS remains relatively low. MGUS patients with venous thromboembolic events were younger at diagnosis.